Co-firing of lignite with peat and white pine in a pilot scale bubbling fluidized bed air - emissions and feedstock reactivity - Badour, Chadi (My University, 2010)
The increasing awareness of the environmental impact of fossil fuels (mainly coal) combustion, which leads to high levels of CO 2 , NO x , SO 2 , mercury and particulate emissions, has motivated research for potential alternatives such as switching from fossil fuels to biomass, or co-firing of both fuels. Co-firing proved to be a promising technology for large scale use of biomass for energy production, as it makes use of the extensive infrastructure associated with the existing coal-based power systems, and requires only relatively modest additional capital investment to achieve a significant CO 2 reduction. The research objectives of the present work were to: (1) Investigate on combustion/cofiring lignite and woodwaste/peat in a 16.19 kW pilot-scale fluidized-bed combustor, and effects of fuel-blending ratios, excess air, particle size and moisture contents on CO 2 , CO, SO 2 , and NO x emissions in the combustion/co-combustion; and (2) Study the combustion reactivity of lignite, woodwaste, peat, and the blended fuels using thermogravimetric analysis (TGA). The combustion/co-combustion behaviour and kinetics of lignite, peat and woodwaste (white pine sawdust) and their blends were investigated using non-isothermal thermogravimetric analysis (TGA) technique. The TGA experiments were performed for pure fuels and compared to blended fuels with respect to their performance in air over a temperature range of 25-700 °c and at a heating rate of 20°C/min. The overall kinetic de-volatilization-combustion reactions for these fuels and their blends were evaluated using the power law model. Using the differential thermal analysis (DTA) data and applying the least square multi-linear regression method, kinetic parameters for the overall devolatilization/combustion reactions including the apparent activation energy ( E a ) , reaction order ( n ) and the pre-exponential ( A ) factor were calculated for each homogeneous fuel and the lignite-peat or lignite-pine sawdust blended fuels (50 wt%-50 wt%%). The wood waste and peat demonstrated a higher reactivity when compared to lignite. The activation energies for lignite, peat, and white pine were determined to be 124.10 kJ/mol, 83.95 kJ/mol, and 98.23 kJ/mol, respectively. Compared with the devolatilization/combustion of homogenous solid fuels, blending peat/white pine with lignite resulted in synergistic effects, enhancing the combustion reactivity of each component fuel.
Keywords: Biomass energy; Coal-burning power plants; Wood waste as fuel; Coal; Combustion; Peat; Lignite; Co-combustion